2016
DOI: 10.12659/msm.897258
|View full text |Cite
|
Sign up to set email alerts
|

Fascin Induces Epithelial-Mesenchymal Transition of Cholangiocarcinoma Cells by Regulating Wnt/β-Catenin Signaling

Abstract: BackgroundOur preliminary study suggested that the expression of Fascin was increased in cholangiocarcinoma, which indicating poor prognosis The present study aimed to explore the roles and mechanisms of Fascin during the progression of cholangiocarcinoma.Material/MethodsWe evaluated the knockdown effect of endogenous Fascin expression by Short hairpin RNA (shRNA) in QBC939 cells. Cell proliferation was confirmed by MTS assay. Migration and invasion assay was used to examine the cell invasive ability. Tumorige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…Machesky and Li found that the high expression of Fascin protein is positively correlated with the low expression of E-cadherin; Fascin protein can induce the occurrence of EMT and knocking out Fascin protein can inhibit the occurrence of EMT and tumor invasion. [25][26][27] Our study also found that Fascin expression in IPA was higher than that in NIPA, and the expression level was positively correlated with Knosp's imaging classification. 28 Thus, Fascin may be an important protein marker that causes pituitary adenomas to invade the periphery.…”
Section: Discussionsupporting
confidence: 57%
“…Machesky and Li found that the high expression of Fascin protein is positively correlated with the low expression of E-cadherin; Fascin protein can induce the occurrence of EMT and knocking out Fascin protein can inhibit the occurrence of EMT and tumor invasion. [25][26][27] Our study also found that Fascin expression in IPA was higher than that in NIPA, and the expression level was positively correlated with Knosp's imaging classification. 28 Thus, Fascin may be an important protein marker that causes pituitary adenomas to invade the periphery.…”
Section: Discussionsupporting
confidence: 57%
“…In particular, the Wnt/β-catenin signaling pathway controls many cellular processes, but was also reported to be deregulated in many type of cancers including breast (23). Indeed, we have previously reported that fascin activates FAK (5,7), and another study demonstrated fascin triggering of β-catenin signaling in cholangiocarcinoma (15). Moreover, FAK was reported to be critical for β-catenin signaling and transcriptional activation of its target genes (9).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of breast cancer cells with 12-O-tetradecanoylphorbol 13-acetate activates the STAT3α and β-catenin signaling pathways, which promotes fascin gene transcription and augments cell migration (14). It is important to note that while fascin is a target of the β-catenin signaling pathway, it was also reported to activate Wnt/β-catenin signaling to promote epithelial-to-mesenchymal transition (EMT) of colon cancer cells (15). Moreover, expression of matrix metalloprotease 2 (MMP2) and MMP9, which we have previously reported to be controlled by fascin in breast cancer cells (4), has been described as downstream targets of the β-catenin signaling pathway (16).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the overexpression of non-membranous β-catenin, a major regulator of the EMT, was also identified in these patients [39]. The study by Mao et al [40] described that fascin promotes EMT of CCA cells by increasing the nuclear and decreasing the plasma membrane localization of β-catenin. In QBC939 cells, knockout of endogenous Fascin expression by short hairpin RNA (shRNA) inhibited EMT, cellular proliferation and invasion, and tumor volume.…”
Section: Role Of Wnt/β-catenin In Epithelial-mesenchymal Transition Imentioning
confidence: 93%